Missional insights on socio-political realities, religious vulnerability, and the choice of Barabbas - Ferreira, Ignatius W. (HTS teologiese studies, 2025)
This article presents a missional perspective on the complex interplay between socio-political realities, religious vulnerability and the formation of political ideologies among Western Christians, drawing insights from the biblical narrative of the choice of Barabbas at Jesus’s trial. In today’s world, Western Christians are confronted with numerous socio-political challenges that can compromise their spiritual discernment, leading to religious delusion and, potentially, the adoption of politicised ideologies. Through a deep dive into the Jewish choice of Barabbas over Jesus, we seek to unravel the underlying dynamics. By examining the socio-political context of Roman occupation and Jewish societal pressures, we illuminate how these external factors influenced the religious vulnerability of the Jewish people. Furthermore, we explore how this vulnerability manifested in the decision to prefer Barabbas, a figure representing worldly resistance, over Jesus Christ, the embodiment of divine grace. From a missional perspective, we reflect on the implications of this historical event for contemporary Western Christian engagement with socio-political issues. We argue that understanding the delicate interplay between socio-political context, religious vulnerability and political ideology is essential for Western Christians seeking to embody the transformative mission of Christ in today’s world.Contribution: This article contributes to missional theology by offering insights into how believers can navigate socio-political complexities with spiritual discernment and faithful witness.